Paradigm for Art Education; Creation Story of Jewels, Theme, Design, Artwork, 3D - ULUSMAN, LEYLA (ELSEVIER SCIENCE BV, 2012)
Theme, design artwork and sizing are the main characters for the history of creation in jewelry art. In other words, you can discover a masterpiece in this history of creation. Marmara University, School of Jewellery Technology and Design have a compact educational program for design and production of jewellery. The School is open to an international attendance. That's why education programs are in English. Our school has tried to get in touch with the similar school in the world for changing students and educators. If the students want to enter secretive world of jewellery art, they should be educated for design, technical processes, gemstone design, cutting and setting with remarkable methods in our school. In this announcement, the history of create a jewel: Theme, design artwork and sizing will be announced and will impress why design is important.